PRINSIP UMUM PENATALAKSANAAN CEDERA OLAHRAGA HEAT STROKE - Saharun Iso, Ade Tobing (Departement of Sports Coaching, Faculty of Sports Sciences, Universitas Negeri Yogyakarta, 2016)
ABSTRACTExercises that are conducted in an extreme heat environment can cause heat injury. Heatinjury is associated with disturbance to temperature regulation and cardiovascular systems. Heatstroke is the most severe type of heat injury. Heat stroke is associated with high morbidity andmortality numbers, particularly if therapy treatment is delayed. In general, heat stroke is caused bytwo things, namely increase in heat production and decrease in heat loss.Heat stroke signs include: (1) rectal temperature above 40.5°C; (2) hypotension,tachycardia, tachypnea; (3) changes in mental status (e.g. irritability, ataxia, confusion,disorientation, syncope, hysteria, and coma); (4) reduced ability to lower body temperature (e.g.stop sweating and skin becoming hot); (5) signs of a life-threatening: disseminated intravascularcoagulant or DIC (e.g. epistaxis, bleeding from intravenous line, bruises, and pulmonary edema)and signs of Acute Renal Failure or ARF (e.g. peripheral edema). Symptoms of heat stroke includefatigue, headache, nausea, and vomiting.Management of heat stroke injuries is by continuously performing cooling down as quicklyas possible while resuscitating patient. Intensive care must be carefully considered to the respiratorytract, reducing body temperature, limiting the production of heat, optimizing air circulation andmonitoring and treating complications. Quick decrease in body temperature is the most importantthings in treatment.Keywords: Heat injury, heat strokeABSTRAKLatihan yang dilakukan di lingkungan panas yang ekstrim dapat menyebabkan terjadinyacedera panas. Cedera panas berhubungan dengan gangguan terhadap sistem pengaturan suhu dansistem kardiovaskuler. Heat stroke merupakan bentuk yang paling parah dari cedera panas. Heatstroke berhubungan dengan angka morbidilitas dan mortalitas yang tinggi terutama jika penangananterapinya terlambat. Penyebab heat stroke secara umum diakibatkan oleh dua hal, yaitu:peningkatan produksi panas, dan penurunan kehilangan panas.Tanda- tanda Heat stroke meliputi: (1) Suhu dubur di atas 40.5°C; (2) Hipotensi,tachycardia, tachypnea;(3) Perubahan status mental (irritability, ataxia, confusion, disorientasi,syncope, hysteria, dan koma); (4) Berkurangnya kemampuan untuk menurunkan suhu tubuh(berhenti bekeringat, kulit menjadi panas); (5) Tanda-tanda yang mengancam jiwa: disseminatedintravascular coagulant (DIC), termasuk epistaxis, pendarahan dari saluran intra vena ,luka memar,dan edema paru, tanda dari Acute Renal Failure (ARF), termasuk edema periperal. Gejala heatstroke meliputi: kelelahan, pusing, mual, dan muntah.Penatalaksanaan cedera heat stroke yaitu dengan melakukan pendinginan secepat mungkindan terus menerus sambil pasien disadarkan. Perawatan intensif harus diperhatikan dengan cermatuntuk saluran pernapasan, mengurangi suhu tubuh, membatasi produksi panas, mengoptimalkansirkulasi udara dan memonitor serta mengobati komplikasi. Penurunan suhu tubuh dengan cepatmerupakan hal yang terpenting dalam perawatan.Kata kunci: Cedera panas, heat stroke